Controlled coherent dynamics of [VO(TPP)], a prototype molecular nuclear qudit with an electronic ancilla. Issue 36 (13th August 2021) - Chicco, Simone; Chiesa, Alessandro; Allodi, Giuseppe; Garlatti, Elena; Atzori, Matteo; Sorace, Lorenzo; De Renzi, Roberto; Sessoli, Roberta; Carretta, Stefano
Abstract : By a combined theoretical and broadband nuclear magnetic resonance study, we show that [VOTPP] is a coupled electronic qubit-nuclear qudit system suitable to implement qudit-based quantum error correction and quantum simulation algorithms. Abstract : We show that [VO(TPP)] (vanadyl tetraphenylporphyrinate) is a promising system to implement quantum computation algorithms based on encoding information in multi-level (qudit) units. Indeed, it embeds a nuclear spin 7/2 coupled to an electronic spin 1/2 by hyperfine interaction. This qubit–qudit unit can be exploited to implement quantum error correction and quantum simulation algorithms. Through a combined theoretical and broadband nuclear magnetic resonance study, we demonstrate that the elementary operations of such algorithms can be efficiently implemented on the nuclear spin qudit. Manipulation of the nuclear qudit can be achieved by resonant radio-frequency pulses, thanks to the remarkably long coherence times and the effective quadrupolar coupling induced by the strong hyperfine interaction. This approach may open new perspectives for developing new molecular qubit–qudit systems.